2011
DOI: 10.1185/03007995.2011.616192
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the efficacy of quinolone containing otics in comparison to antibiotic–steroid combination drugs in the local treatment of otitis externa

Abstract: With a level Ia evidence, this investigation validates the clinical benefit of quinolones as compared to classic combination drugs in the local treatment of acute otitis externa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…Topical use of antibiotics for treating otitis cases is a common practices followed by practioners. Mosges et al (2011) stated that fluroquinolones had high success rate than non-quinolones in curing the otitis. Enrofloxacin is a drug of choice against Staphylococci in the recurrent and chronic skin problems in our local area (Reddy et al, 2014b).…”
Section: Treatment and Discussionmentioning
confidence: 99%
“…Topical use of antibiotics for treating otitis cases is a common practices followed by practioners. Mosges et al (2011) stated that fluroquinolones had high success rate than non-quinolones in curing the otitis. Enrofloxacin is a drug of choice against Staphylococci in the recurrent and chronic skin problems in our local area (Reddy et al, 2014b).…”
Section: Treatment and Discussionmentioning
confidence: 99%
“…Safety profiles were similar between groups. 40 Similarly, Mösges et al 42 reviewed 12 relevant randomized controlled clinical studies involving 2682 patients and concluded that quinolone therapy achieved a higher cure rate (P = .01) and superior eradication rate (P = .03) than a non-fluoroquinolone-containing antibiotic-steroid combination. The clinical significance of these 2 reviews is reduced, however, when considering that bacterial persistence in the ear canal after treatment does not necessarily imply persistent acute otitis externa symptoms.…”
Section: External Otitis Tympanostomy Tubeassociated Otorrheamentioning
confidence: 99%
“…Kaushik and coworkers 110 reached the same conclusion in their more recent Cochrane review, which included 7 newer trials with more than 1600 patients. In contrast, Mösges and colleagues 129 found superior clinical cure rates for topical quinolones versus other antibiotic-steroid combination drugs (odds ratio, 1.29; 95% CI, 1.06-1.57). However, the validity of this finding must take into consideration industry funding, substantial heterogeneity in the pooled analysis, and the possibility of a trivial effect size as suggested by the lower bound of the 95% CI (near unity).…”
Section: Efficacy Of Topical Therapymentioning
confidence: 95%
“…The clinical significance of this modest effect (NNT of 12 patients) is reduced when considering that persistent bacteria in the ear canal after treatment does not necessarily imply persistent AOE symptoms. Mösges and colleagues 129 also found a higher bacteriologic cure rate when quinolones were used (odds ratio, 1.44; 95% CI, 1.03-2.02). The validity of this finding, however, must again take into consideration industry funding, substantial heterogeneity in the pooled analysis, and possibility of a trivial effect size as suggested by the lower bound of the 95% CI (near unity).…”
Section: Efficacy Of Topical Therapymentioning
confidence: 98%
See 1 more Smart Citation